2016
DOI: 10.21013/jmss.v4.n3.p3
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of Employee Trust Scale

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Seok et al (2014) identified factors contributing to employee trust: status privileges, competency, benevolence, workerleader relationships, and department head integrity. In their subsequent study, Seok et al (2015) emphasized competency, integrity, and work relationships as crucial elements affecting trust. Hill and Lineback (2019) argue that trust is built on managerial competency, technical knowledge, operational expertise, and political acumen.…”
Section: Employees' Trust In Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Seok et al (2014) identified factors contributing to employee trust: status privileges, competency, benevolence, workerleader relationships, and department head integrity. In their subsequent study, Seok et al (2015) emphasized competency, integrity, and work relationships as crucial elements affecting trust. Hill and Lineback (2019) argue that trust is built on managerial competency, technical knowledge, operational expertise, and political acumen.…”
Section: Employees' Trust In Managementmentioning
confidence: 99%
“…Building organizational trust is fundamental to successful leadership, involving trust between leaders and employees and among peers. Leaders play a pivotal role in fostering this trust, with studies by Seok et al (2015), Norman et al (2010), Farmanesh andZargar (2023), andIslam et al (2020) emphasizing the importance of competence, positivity, integrity, and transparency in leaders. Ethical leadership, as suggested by Javed et al (2018) and Zhang et al (2018), significantly influences employees' trust, prompting investigations into its impact on trust levels within different organizational settings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serrat (2017) recommends several factors that management needs to do to develop the trust of employees toward management such as presenting a clear and attainable vision to the employees, living the values of the organization through their own lives, establishing an atmosphere of trust in the organization, decisions must be based on factual and objective data, and compensation must be based on merits. Seok, et al (2015) have also identified three dimensions of trust of employees toward the management namely trust in management competency, trust in management integrity, and trust in the working relationship. T rust in management competency refers to employees' trust in management's ability to carry out their tasks.…”
Section: Employees' Trust In the Managementmentioning
confidence: 99%